Comparative studies on the inhibitory activities of selected benzoic acid derivatives against secretory phospholipase A2, a key enzyme involved in the inflammatory pathway1. Issue 7 (16th July 2015) - Dileep, K. V.; Remya, C.; Cerezo, J.; Fassihi, A.; Pérez-Sánchez, H.; Sadasivan, C.
<x xml:space="preserve">Abstract</x> Inhibitory activities of selected benzoic acid derivatives against phospholipase A2.